Discretion: Whether and How Does It Promote Street-Level Bureaucrats' Taking Charge Behavior? - Yuan, Shuai; Chen, Zhixia; Sun, Mei (Frontiers in Psychology, 2022)
The extant literatures on discretion have mainly focused on its effect on policy implementation and public service delivery but few studies have looked at its influence on street-level bureaucrats’ work behaviour such as taking charge behaviour (TCB), the behaviour that is of great importance to government reforms especially in developing and transitional countries. Based on self-determination theory, this paper examines whether and how discretion promote street-level bureaucrats’ TCB. Two studies were conducted among street-level bureaucrats in China. First, a survey experiment (n=355) suggests that discretion positively predicts street-level bureaucrats’ TCB. Then, a survey questionnaire study (n=442) shows that discretion is positively related to TCB through the mediator of PSM. We conclude with implications for theory and practice.